Duration of epilepsy and severity of the disease in neurosurgical patients - G. V. Odintsova; M. V. Aleksandrov; A. Yu. Ulitin; A. V. Koloteva (Эпилепсия и пароксизмальные состояния, 2018)
The problem of a late referral to surgical treatment in epilepsy was addressed in this study.Objective: To elucidate whether the course of epilepsy is influenced by the duration of the disease.Materials and Methods. A cohort of 91 patients with epilepsy who underwent surgical interventions from 2012 to 2017, were retrospectively studied. The disease dynamics (frequency and type of seizures) as well as the EEG changes were assessed.Results. Of those patients, 77% had epilepsy more than 10 years, and 41% – more than 20 years. The temporal localization was found in 71% of cases, and the extra-temporal – in 29%. In all patients, seizures occurred at least once a month. Secondary generalized seizures were found in 58% of patients, and status epilepticus was observed in 30% of cases.Conclusion. The course of epilepsy in the clinical and neurophysiological terms deteriorates with a long duration of the disease. The present results can be used to determine the optimal time for a referral for surgical treatment.